KARAKTERISTIK PASIEN DI RUMAH SAKIT TINJAUAN ILMU PSIKOLOGI DAN KONSELING - Mellyarti Syarif (Universitas Islam Negeri Imam Bonjol Padang, 2015)
Patients in the hospital do not only need the help of medical services but also they expect psychological support. Psychology and Counseling are disciplines of science that has great access to understanding and helping patients. In-depth study of the characteristics of patients in perspective of psychology and counseling become a reference in providing therapy to the patient. In turn, the contribution of psychology and counseling about the characteristics of patients in the hospital is expected to contribute in efforts to accelerate the patient's recovery.